Mental toughness and perfectionism in judo: differences by achievement and age. The relation between constructs - Suarez-Cadenas, E.; Sretkovic, T.; Perales, J. C.; Petrovic, J.; Sterkowicz-Przybycien, K.; Batez, M.; Drid, P. (Archives of Budo, 2016)
Background and Study Aim: The relationship between mental toughness (MT) and perfectionism has not been established to date. The main aim of this study is: knowledge about MT, perfectionistic strivings, and perfectionistic concerns of judo athletes by achievement level and age; relationship between MT and perfectionism dimensions.